PENERAPAN SISTEM PAKAR BERBASIS FRAME UNTUK IDENTIFIKASI JENIS PADA RAS KUCING - Ira Puspita Sari; Liza Trisnawati; Nia Silviana (LPPM Universitas Abdurrab, 2023)
There are already many cat-loving communities in Indonesia, one of which is in the city of Pekanbaru. Most cat lovers in the community are still unaware of the breeds of cats they keep. Departing from these problems, an expert system was created to identify cat breeds to help cat lovers know exactly the breed of cats being kept. The system is made to apply a frame-based method for the representation of its knowledge, the method is applied to obtain cat breed results based on physical characteristics owned and firebase as a place to store data. Data collection in the form of literature research, interviews and observations. The research process uses quantitative methods by conducting tests. The cat breed expert system was tested using black box testing successfully and the User Accaptance Test (UAT) was carried out by obtaining an average score of 88.06% from 58 cat lovers. This Expert System is expected to help cat lovers know exactly the breed of cats being kept.